Pengaruh asap rokok pada peningkatan konsentrasi PM2.5 dan PM10 di ruang tamu akibat merokok di dalam dan di luar rumah - Nuryati, Neneng; Sumeru, Kasni; Setyawan, Andriyanto; Hikmat, Yudi Prana; Sumeru, Husain Akbar; Sukri, Mohamad Firdaus (Program Studi Ilmu Lingkungan SekolahPascasarjana UNDIP, 2024)
Clean air is a basic need to ensure the health of the occupants in ahouse. Cigarette smoke is one of the pollutants that are often present at home. The negative effects of cigarette smoke on health have been reported by expertsall over the world. However, until now, there are still many smokers who smoke anywhere around the house, such as on the terrace, in the living room, and in the bathroom. This behavior will have a negative impact on the air quality in the house. Particulate matter with a diameter ofless than 2.5 μm (PM2.5) and less than 10 μm (PM10) is one of the main pollutants produced by cigarette smoke. Based on several previous studies, it wasreported that apart from settling in the lungs, PM2.5 and PM10 can cause several diseases, including asthma, ARI (acute respiratory infection), lung cancer, and increase mortality rates. In this study PM2.5 and PM10 were measured in the living room due to smokers smoking in the bathroom, in the living room, and on the terrace. PM2.5 and PM10 concentrationswere measured in a house with an area of about 45 m2. Data collection was carried out before smoking, 15 minutes after the cigarette was lit, and 30 and 60 minutes after the cigarette was extinguished. Based on the measurements, it was found that the concentrations of PM2.5 and PM10 in the living room will higher than that ofthe quality standard for all smoking locations in the house area. Even though the smoker smoked on the terrace with the living room door completely closed, the concentrations of PM2.5and PM10 in the living room continued to increase, from the previous 27 and 68 μg/m3 to 63 and 127 μg/m3. From this study it was concluded that even though smoking outside the home, with the door closed, it can still increase the concentration of PM2.5 and PM10 in the living room much higher than that of the national quality standard. This, of course, will be harmful for all residents of the house.